2005
DOI: 10.1002/adma.200401125
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Bile‐Salt Nanotubes in Water: Kinetics of Formation

Abstract: Preparation of organic structures on the nanometer scale by the spontaneous self-assembly of molecular species is a very active field of research in materials science. Among the various morphologies reported, tubular architectures are of particular interest since they may find applications in catalysis, selective separation, drug release, sensors, containers, and conducting devices in nano-, opto-, or ionoelectronics. A brief review of the topic is given in our previous report in this journal.[1] It has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 8 publications
2
87
0
Order By: Relevance
“…That tubular morphology is lost at higher temperature, once lipid flip-flop is kinetically feasible, resulting in the formation of large liposomes. ii) Bean et al, [7] have studied the kinetics of the formation of sodium lithocholate nanotubes. After examining different possibilities, they concluded that the mechanism involved in the tube formation is complex, because coaxial cylinders, helical ribbons, fibrils, and singlewalled tubes were found to coexist in the first stage of the kinetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That tubular morphology is lost at higher temperature, once lipid flip-flop is kinetically feasible, resulting in the formation of large liposomes. ii) Bean et al, [7] have studied the kinetics of the formation of sodium lithocholate nanotubes. After examining different possibilities, they concluded that the mechanism involved in the tube formation is complex, because coaxial cylinders, helical ribbons, fibrils, and singlewalled tubes were found to coexist in the first stage of the kinetics.…”
mentioning
confidence: 99%
“…ii) They self-organize in different structures both in the solid state and in aqueous solution. For example, in aqueous solution they self-aggregate to form micelles, [3,4] gels, [5] fibers, [6] nanotubes, [7] or laminar structures. [8] In such processes, the number, location, and configuration of the hydroxyl groups play a leading role.…”
mentioning
confidence: 99%
“…Recently, FFR, direct-imaging cryo-TEM, and SAXS studies were performed to elucidate the early structures leading to the formation of the uniform tubes (Figure 3). Direct-imaging cryo-TEM images showed that less than 2 min after initiating the process by mixing LCA powder in aqueous NaOH solution, single-and multi-walled tubules of different diameters were formed [4]. Other intermediates, including helical ribbons and thin long fibers, were also observed within the first 30 min.…”
Section: Cryo-tem Investigations Of Lmog Gelsmentioning
confidence: 94%
“…In some cases, direct images provide the only way to prove a suggested or a theoretically predicted model. That was demonstrated for example in the case of the theoretically predicted branched micelles [1], the shape of the "end-caps" of thread-like micelles [2,3], and the exact nanostructure and mechanism of formation of lithocholate nanotubes [4,5].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation